PENERAPAN PEMBELAJARAN KONTEKTUALUNTUK MENIGKATKAN AKTIFITAS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS V A SD NEGERI 33 RAWANG BARAT - Yasmizar, Yasmizar; Rismen, Sefna; Aima, Zulfitri (Pendidikan Matematika, 2014)
ABSTRAKÂ The low student learning outcomes and student activities in math , especially on the operations of material fractions in grade V Elementary School 33 West Rawang reflected in the average value of daily tests are still below the minimum completeness kreteri ( KKM ) which has been set at the beginning of the school year namely the classical completeness kreterial 75 and 80 % of the number of students . This study was conducted at the VA grade Elementary School 33 West Rawang where the procedures of the study consisted of four phases: planning , given action , observation and evaluation , and the last doing analysis and reflection . Data collection techniques taken from the students during learning activities and the results of tests of learning takes place . The success criteria as a benchmark in this study in the classical 80 % of the total student has reached the KKM. Dari study conducted on two cycles obtained a description of learning outcomes is an increase in the first cycle the average value of learning outcomes increased Â 66.43 to 79.9 the second cycle . Students in learning activities also showed that 59.5 % improvement in the first cycle , increased to 87.8 % in the second cycle . This indicates that the approach can increase the activity of contextual learning and student learning outcomes then the hypothesis proposed action is acceptable .